PETROGENESIS OF ALKALINE VOLCANIC ROCKS OF THE KETKAP-YUNA MAGMATIC PROVINCE OF ALDAN - Polin V.F.; Sakhno V.G. (My University, 2004)
Very characteristic formations are considered representing alkaline-salic rocks association with granitoids. The Bokurskii volcano-pluton is investigated, in which large fragments of volcano-pluton structure fragments are retained in collapse formations. Analysis of petro- and geochemical diagrams allows suggesting that the different-basic groups of Bokurskii complex' alkaline rocks are inter-connected by fractional differentiation relations, and development of its series of rocks with similar petrogeochemical parameters is determined by the especial petrogenetic mechanism.